The Correlation Between Emotional Quotient and Students’ Learning Achievement on English - Yolanda, Sisra; Eliza; Prima Dewi, Merry; Safitri, Loli (BiCED Proceeding, 2023)
The main of research question of this study was “Is there any correlation between students’ emotional quotient and their learning achievement on English?”. The Problem of this research was some students had high emotional quotient but low learning achievement in English, and some students had low emotional quotient but high learning achievement in English. The objective of this research was investigate the relationship between students' emotional quotient and their learning achievement on English. The design of this research was correlation design. This research was conducted at UPT SMPN 1 Tanjuang Baru. This research included population of 74 students. Technique of data collection was used questionnaire and documentation. Technique of data analysis was used SPSS 25. The result was 0,548. There was a positive correlation between students’ emotional quotient and their learning achievement on English. Based on hypothesis testing, the rxy was 0.548 whereas r - table on α = 0.05 was 0.2319. It means that rxy score was bigger than r - table score. Hence, Ha was accepted and Ho was rejected. It was found that there was a positive correlation between emotional quotient and students’ learning achievement in English of eighth grade students at UPT SMPN 1 Tanjuang Baru.